2017
DOI: 10.1149/2.1021706jes
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Oxidation Behavior of Ni-Cr Alloys in CO2Gas Atmosphere

Abstract: Model Ni-Cr alloys containing 5, 10, 15, 20, 25 and 30 wt% Cr were oxidized in Ar-20 vol% CO 2 gas mixtures at temperatures of 650, 700 and 800 • C. In general, multi-layered oxide scales were observed on the surface after reaction. With increased alloy Cr content, the oxide structure changed from external NiO, plus intermediate inner oxides and an internal oxidation zone, to forming a thin chromia band at the base of the oxide scale and, at higher Cr levels, an exclusive chromia scale. Increasing temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 36 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…However, deviations from the parabolic kinetics during the steady-state oxide scale growth period have frequently been observed. Several interpretations have been used to explain such deviations, including a phase-boundary process as the rate-determining step of the reaction, , built-in electric field driven ionic diffusion, , doping effect in the oxide scale, and microstructure evolution effect on the oxide scale growth. The reverse reaction is often ignored to explain the deviations from the parabolic kinetics of the scale oxide growth. As shown from our results of the CO 2 -induced Ni oxidation, the reverse element of the reaction indeed exists and should be taken into account to understand the overall reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…However, deviations from the parabolic kinetics during the steady-state oxide scale growth period have frequently been observed. Several interpretations have been used to explain such deviations, including a phase-boundary process as the rate-determining step of the reaction, , built-in electric field driven ionic diffusion, , doping effect in the oxide scale, and microstructure evolution effect on the oxide scale growth. The reverse reaction is often ignored to explain the deviations from the parabolic kinetics of the scale oxide growth. As shown from our results of the CO 2 -induced Ni oxidation, the reverse element of the reaction indeed exists and should be taken into account to understand the overall reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…This result is the same as that observed on commercial alloys in Figure 9. However, as the temperature increased, the oxidation rates of Fe20Cr, Ni25Cr and Ni30Cr binary model alloys unexpectedly decreased [47,73]. The different result is closely related to the diffusion rate of Cr and the Cr content of the alloy.…”
Section: Effects Of Environmental Parametersmentioning
confidence: 92%
“…These previous results indicate that chromia-forming nickel-base alloys have higher carbonization resistance than chromia-forming iron-base alloys. Surprisingly, the intergranular carbides were revealed by etching in Ni25Cr and Ni30Cr model alloys after exposure to 650 • C/1 bar Ar-20%CO 2 gas for 500 h but not in Ni20Cr [47]. When the temperature was up to 800 • C, the Ni20Cr model alloy also formed the intergranular carbides.…”
Section: Carburization Resistancementioning
confidence: 95%
See 1 more Smart Citation
“…The Ni-Cr protective layers provide excellent mechanical properties, high creep resistance, and adequate chemical resistance at elevated operating temperatures—such as high corrosion resistance. The effect of temperature on the oxidation behavior of binary Ni-Cr alloys in the CO 2 gas atmosphere has been studied in [ 7 ] and it was shown that at 650 °C, the oxidation rates were not significantly decreased until the alloy Cr content reached 30% (wt.). At a temperature of 800 °C, the oxidation rates of Ni-5Cr, Ni-10Cr, and Ni-15Cr alloys continued to increase, while those of alloys with 20 wt.% Cr and above reduced due to protective external chromia scale formation.…”
Section: Introductionmentioning
confidence: 99%